2020
DOI: 10.1002/qre.2754
|View full text |Cite
|
Sign up to set email alerts
|

Exploitability prediction of software vulnerabilities

Abstract: The number of security failure discovered and disclosed publicly are increasing at a pace like never before. Wherein, a small fraction of vulnerabilities encountered in the operational phase are exploited in the wild. It is difficult to find vulnerabilities during the early stages of software development cycle, as security aspects are often not known adequately. To counter these security implications, firms usually provide patches such that these security flaws are not exploited. It is a daunting task for a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Specifically, these authors pre-trained a DL model, BERT [42], on massive non-SV sources (e.g., text on Book Corpus [211] and Wikipedia [60]) and then fine-tuned this pre-trained model on SV data using additional pooling and dense layers. Bhatt et al [14] also suggested that incorporating the types of SVs (e.g., SQL injection) into ML models can further enhance the predictive effectiveness. Suciu [176] empirically showed that unifying SV-related sources used in prior work (e.g., SV databases [20], social media [159], SV-related discussions [179] and PoC code in ExploitDB [84]) supports more effective and timely prediction of functional exploits [58].…”
Section: Exploit Likelihoodmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, these authors pre-trained a DL model, BERT [42], on massive non-SV sources (e.g., text on Book Corpus [211] and Wikipedia [60]) and then fine-tuned this pre-trained model on SV data using additional pooling and dense layers. Bhatt et al [14] also suggested that incorporating the types of SVs (e.g., SQL injection) into ML models can further enhance the predictive effectiveness. Suciu [176] empirically showed that unifying SV-related sources used in prior work (e.g., SV databases [20], social media [159], SV-related discussions [179] and PoC code in ExploitDB [84]) supports more effective and timely prediction of functional exploits [58].…”
Section: Exploit Likelihoodmentioning
confidence: 99%
“…However, the LDA topics/keywords did not agree well (< 40%) with the OWASP descriptions, probably because 10 topics did not cover all the underlying patterns of SV descriptions. Aljedaani et al [3] again used LDA to identify 10 types of SVs reported in the bug tracking system of Chromium 14 and found memory-related issues were the most prevalent topics.…”
Section: Custom Vulnerability Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Sabottke et al [17] developed an exploit prediction model using a dataset acquired from Twitter having links to CVE-IDs and from Symantec threat signatures for the positive labels. Of late, Almukaynizi et al [18] deduced a model that considers data from various sources to predict the likelihood of exploitation, and Bhatt et al [19] developed an exploit prediction framework and claimed it a highly effective approach for the exploit that could be seen in the wild.…”
Section: Literaturementioning
confidence: 99%